Development and evaluation of a millet-based infant food fortified with plant protein - Dartey, Florence Akpene (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Philosophy in Biochemistry.